Reseña de Marmaridou, s. (2000) Pragmatic meaning and Cognition (Pragmatics and Beyond New Series), Amsterdam/ Philadelphia, John Benjamins Publishing Company. - José María García Núñez; M. Carmen Merino Ferrada (Pragmalingüística)
Se trata de una reseña sobre Marmaridou, s. (2000) Pragmatic meaning and Cognition Pragmatics and Beyond New Series), Amsterdam/ Philadelphia, John Benjamins Publishing Company.